Social Capital in Mangrove Utilization for Silvofishery: Case Study in Kutai National Park, Indonesia - Iin Sumbada Sulistyorini; Erny Poedjirahajoe; Lies Rahayu Wijayanti Faida; Ris Hadi Purwanto (Jurnal Manajemen Hutan Tropika, 2018)
Social capital has an important role in mangrove management on conservation areas. Utilization of mangrove forest with silvofishery system can be an alternative developed for the community around the conservation areas. The purpose of this research is to know the strength of social capital in supporting the utilization of mangrove for silvofishery. This research adopted Social Capital Assessment Tool method and data analysis with Partial Least Square-Structural Equation Modeling. The results of the study found that there were several elements of social capital in five study villages that have not supported silvofishery in Kutai National Park (KNP), East Kalimantan, Indonesia. The overall analysis of the respondents showed that there were five elements of social capital have significant effect on silvofishery. The other two elements were insignificant and should be of particular concern to be improved, i.e. social networks and social norms. Indicators to be aware of were the increased knowledge of communities on park-related regulations, increased involvement of individuals in the community, and the strengthening of public figures who can be role models for the community. Mangrove forest of KNP should be kept as conservation area, but it should still pay attention to the socio-economic conditions of the surrounding community. The strength of social capital is expected to realize conservation-based economic development.